Pharmacogenetics of CYP2D6 and CYP2C19 as a pre-prescription tool for drug efficacy and toxicity in a demographically-representative sample of theSouth African population - Pepper, Michael Sean (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.